Cancer morbidity in British military veterans included in chemical warfare agent experiments at Porton Down: cohort study. (24th March 2009) - Carpenter, L M; Linsell, L; Brooks, C; Keegan, T J; Langdon, T; Doyle, P; Maconochie, N E S; Fletcher, T; Nieuwenhuijsen, M J; Beral, V; Venables, K M
Abstract : Objective To determine cancer morbidity in members of the armed forces who took part in tests of chemical warfare agents from 1941 to 1989. Design Historical cohort study, with cohort members followed up to December 2004. Data source Archive of UK government research facility at Porton Down, UK military personnel records, and national death and cancer records. Participants All veterans included in the cohort study of mortality, excluding those known to have died or been lost to follow-up before 1 January 1971 when the UK cancer registration system commenced: 17 013 male members of the UK armed forces who took part in tests (Porton Down veterans) and a similar group of 16 520 men who did not (non-Porton Down veterans). Main outcome measures Cancer morbidity in each group of veterans; rate ratios, with 95% confidence intervals, adjusted for age group and calendar period. Results 3457 cancers were reported in the Porton Down veterans compared with 3380 cancers in the non-Porton Down veterans. While overall cancer morbidity was the same in both groups (rate ratio 1.00, 95% confidence interval 0.95 to 1.05), Porton Down veterans had higher rates of ill defined malignant neoplasms (1.12, 1.02 to 1.22), in situ neoplasms (1.45, 1.06 to 2.00), and those of uncertain or unknown behaviour (1.32, 1.01 to 1.73). Conclusion Overall cancer morbidity in Porton Down veterans was no different from that in non-Porton Down veterans.